Pre-martensite and bainite reactions: A thermal stability study - Aleksandra Królicka; José Antonio Jimenez; Francisca G. Caballero (Materials & Design)
The comparative analysis of two ways to achieve ultra-fine bainitic steels considering isothermal heat treatment above and below martensite start (Ms) temperature was formulated. Although the presence of pre-martensite below the Ms temperature accelerates the nucleation time of the bainitic transformation, the time to finish the transformation is longer (∼11.5 h) compared to the treatment above Ms (∼5 h). A qualitative and quantitative analysis of the morphology of the bainitic structure demonstrated that there are no significant differences in the thickness of the bainitic ferrite laths in both cases. However, a clear refinement of the retained austenite blocks of the steel treated below Ms was observed. Moreover, TEM and STEM/EDS studies revealed precipitation processes associated with the decomposition of the metastable bainitic and bainitic-martensitic structures during the tempering. It was shown that both heat treatment routes lead to secondary hardening during the tempering at 550 °C. At lower tempering temperatures, the bainitic matrix obtained above Ms was characterized by higher thermal stability, while the presence of pre-martensite in the steel treated below Ms has greater effectiveness in the secondary hardening effect at higher tempering temperatures and therefore in thermal stability of bainite at the high-temperature tempering range. These results provide a new perspective for designing heat treatment processes for advanced bainitic steels in applications subjected to operation at elevated temperatures.